2020
DOI: 10.7717/peerj.9620
|View full text |Cite
|
Sign up to set email alerts
|

How “dirty” is the Dark Triad? Dark character profiles, swearing, and sociosexuality

Abstract: Malevolent character traits (i.e., the Dark Triad: Machiavellianism, narcissism, and psychopathy) are associated to emotional frigidity, antagonism, immoral strategic thinking, betrayal, exploitation, and sexual promiscuity. Despite the fact that character is a complex adaptive system, almost every study has solely investigated the linear association between malevolent character and attitudes towards both swearing and sociosexual orientation (i.e., behavior, attitude, and desire regarding promiscuous sexual be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…DT traits are associated with several types of negative psychosocial outcomes and these results are not surprising because the dark traits themselves are partly included in those characteristics typical of individuals who manifest some type of malevolent and/or antisocial behavior. Overall, studies found a strong association between DT traits and the tendency to take financial hazard [102], disposition toward risky driving [103], health-risk activities, such as substance use and sexual promiscuity [68,104], aggression [105,106], bullying, cyberbullying [107,108], and crime [109]. Nevertheless, there is specific literature showing the advantages of scoring high DT traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DT traits are associated with several types of negative psychosocial outcomes and these results are not surprising because the dark traits themselves are partly included in those characteristics typical of individuals who manifest some type of malevolent and/or antisocial behavior. Overall, studies found a strong association between DT traits and the tendency to take financial hazard [102], disposition toward risky driving [103], health-risk activities, such as substance use and sexual promiscuity [68,104], aggression [105,106], bullying, cyberbullying [107,108], and crime [109]. Nevertheless, there is specific literature showing the advantages of scoring high DT traits.…”
Section: Discussionmentioning
confidence: 99%
“…The Dark Triad is positively associated with risk involvement and negatively associated with risk perception [101]. Studies found a strong association between DT traits and the tendency to take financial hazard [102], disposition toward risky driving [103], health-risk activities, such as substance use and sexual promiscuity [68,104], deviant behaviors, such as aggression [105,106], bullying, cyberbullying [107,108], and crime [109]. Studies demonstrated that psychopathy and narcissism represent the most harmful dark factors in relation to risky activities [29,100], contrarily to Machiavellianism [29].…”
Section: Dark Triad Risky Behaviors Antisocial and Criminal Behaviorsmentioning
confidence: 99%